(untitled) (International Journal of Innovative Computing, 2023)
The existing inventory control and management systems are bedevilled with issues such as lack of implementation, non-generalization, susceptibility to subjectivity, measurement error, and low reliability, among others. This paper presents a Just-in-Time platform that could overcome some of these inventory management issues. The platform comprises customer, demand planning, supply and production control interfaces. The customer interface provides the basis of interaction between the user and the system and was designed with friendliness, efficiency and enjoyable tendencies while facilitating a seamless operation. The demand planning interface comprises sales and demand planning components for online receipt and processing of sales orders and verifications of customers’ personal information and payment details. The supplier interface is required for receipt of manufacturing orders and supply by the production schedule. The production planning control interface handles the production items, time, and quantities and so on. It was designed to provide capacity for speedy production to meet agreed or projected demand. The experimental study of the model on the ordering management of two production companies in Lagos, Nigeria confirmed its positive impact on the production cycle, turnover and holding cost with its 95% fulfilment of orders compared to 73% recorded for the non-JIT ordering. It was also revealed that the use of Just-in-Time (JIT) led to a 59.34% gain in profit and 12.73% reduction in expenditure.